Assessment of Some Heavy Metals and Trace Elements in a Sample of Patients with Viral Hepatitis in Baghdad - Najlaa Fattah-Allah Rasheed; Hind Salman Jassim; Ahmad Saadi Hassan (Journal of Techniques)
The liver is a vital metabolic organ that performs a variety of complex biochemical functions such as metabolism, detoxification, and excretion. Impairment of liver functions disrupts trace element metabolism, causing oxidative stress, which subsequently leads to liver inflammation and fibrosis. This study aims to evaluate zinc (Zn), copper (Cu), iron (Fe), cadmium (Cd), and lead (Pb) levels in chronic viral hepatitis (HBV or HCV) patients in Baghdad. One hundred fifty samples of blood were collected from fifty patients with hepatitis B, fifty patients with hepatitis C, and fifty individuals without viral hepatitis as controls at the Gastroenterology and Hepatology Teaching Hospital in Baghdad during the period from November 2021 to March 2022. Patients with viral hepatitis had highly significant elevated levels of lead, cadmium, and copper compared with the controls (P-value = 0.000), whereas zinc and iron levels were highly significantly lower in the patient groups than in the control group (P-value = 0.000). In conclusion, viral hepatitis patients showed varying levels of zinc, copper, iron, cadmium, and lead compared to healthy controls.